Design of Single Atom Catalysts - Yu, Zuran; Xu, Haoxiang; Cheng, Daojian (Advances in physics: X, 2021)
Over the past decade, computational modeling based on density functional theory (DFT) calculations provides a deep insight into the catalytic mechanism of single-atom catalysts (SACs) and paves way for high-throughput screening of promising SACs. This review summarizes computational methods for the analysis of the electronic structures and catalytic performance of SACs, as well as introduces the utilization of descriptors for the computational design of SACs. We expect that future advances in computational methods will surely help to identify highly effective SACs for a wide variety of reactions.